Can Nanosecond Laser Achieve High‐Performance Perovskite Solar Modules with Aperture Area Efficiency Over 21%?. Issue 41 (2nd September 2022) - Gao, Yanyan; Liu, Chong; Xie, Yi; Guo, Rilang; Zhong, Xuqi; Ju, Huanxin; Qin, Li; Jia, Peng; Wu, Shaohang; Schropp, Ruud E. I.; Mai, Yaohua
Abstract: Overcoming cell‐to‐module (CTM) efficiency losses is indispensable to realize large‐area high‐efficiency perovskite photovoltaic devices for commercialization. Laser scribing technology is used to fabricate perovskite modules, but it does not seem to solve the problem of high‐quality interconnection and high geometric filling factor (GFF), which are the prerequisites for overcoming CTM losses. In reality, what kind of laser technology is needed to fabricate high‐efficiency perovskite solar modules is still an open question. Herein, this work demonstrates that a nanosecond pulse laser is able to deliver a reduced heat‐affected zone due to the small thermal diffusion coefficient ( D t ) of perovskite material, contributing to the accomplishment of a high GFF of up to 95.5%. In addition, the monolithic interconnection quality is improved by finely lifting off the capping layers on indium tin oxide and identifying the residue within the scribed area. As a result, a certified aperture area efficiency of 21.07% under standard 100 mW cm −2 AM1.5G illumination is achieved with a high photovoltaic fill factor exceeding 80%. The present study provides guidance in overcoming key CTM efficiency losses in perovskite photovoltaic technology. Abstract : Expensive picosecond/femtosecond laser technologies may solve the problem of considerable cell‐to‐module efficiency losses for perovskites, but it is not necessarily the best option for industrialization. This work demonstrates that a nanosecond pulse laser is able to deliver a high‐quality interconnection and high geometric filling factor for perovskite solar modules with a certified efficiency of 21.07%.